Case Report: Unexplained Fever and Chest Pain in a 5-Year-Old - Lubocka, Paulina; Sabiniewicz, Robert (Frontiers in Pediatrics, 2021)
Pericarditis is a rare, but severe cause of chest pain in children that can easily be overlooked during routine diagnostics. Fibrinous pericarditis was recognized in a five-year old patient who presented with fever and chest pain. Despite thorough diagnostics, no evident etiological factor was found. Furthermore, the disease was unresponsive to broad-spectrum antibiotics and NSAIDs, however oral prednisone was found to cause rapid improvement in the patients’ condition. It was presumed that the patient’s condition was caused by a blunt trauma to the chest experienced three days prior to the onset of symptoms. In an 8-month follow-up the patient remains in good overall condition and no recurrences were observed.